Evolutionary responses of Escherichia coli to phage pressure: insights into mucoidy and colanic acid overexpression - Laurie C. Piché; Sophie Bories; Viacheslav Liato; Valérie E. Paquet; Linda Saucier; Marie-Pierre Létourneau-Montminy; Steve J. Charette; Rodrigue Dubar; Simon J. Labrie; Patrick Lagüe; Antony T. Vincent (BMC Genomics)
Abstract Background Antibiotic resistance is a major issue affecting all spheres of human activity, including agriculture. One significant example is the Avian Pathogenic Escherichia coli (APEC), a bacterium that infects poultry and leads to substantial economic losses in the farming industry. As antibiotics lose efficacity, bacteriophages (phages) —viruses that specifically target bacteria—are emerging as a promising alternative to antibiotics for treating and preventing bacterial infections. However, bacteria can develop resistance to phages through various mechanisms. Studying the coevolution between a phage and its host bacterium is important to gain insight into the phage's potential as a therapeutic agent. This study investigates the evolutionary responses of an APEC strain and a laboratory E. coli strain to a commercial phage originally isolated from APEC. Results In most cases, phage resistance resulted in a significant increase in mucoidy. Genomic analysis revealed that this resistance consistently correlated with amino acid changes, particularly in proteins involved in colanic acid production, such as YrfF. Further investigation of a mutation found in the YrfF protein demonstrated that this mutation altered the protein’s structure and its interaction with the membrane. Transcriptomic analysis confirmed that the genes involved in colanic acid production were significantly overexpressed. Although the strains possessed a CRISPR-Cas system, it did not contribute to phage resistance. Conclusions This study suggests that specific amino acid changes in key proteins may be a mechanism employed by E. coli, including APEC, to defend against phage infections.